2018
DOI: 10.1007/s00296-018-4102-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in early, intensively treated and tight-controlled rheumatoid arthritis patients is frequent and persistent: a prospective study

Abstract: Fatigue has a large impact on quality of life and is still unmanageable for many patients. Study aims were describe (1) the prevalence and pattern of fatigue over time in patients with early rheumatoid arthritis under a treat-to-target strategy and (2) identify predictive factors for worsening and recovering of fatigue over time. Data from the tREACH study were used, comparing different treatment strategies with fatigue as secondary objective. Patient outcomes on fatigue, quality of life, depression, and copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Nearly one in four who were fatigued at the onset of the study showed lower levels of fatigue by 1 year, but one in six of the patients who were not initially fatigued recorded increased fatigue. 30…”
Section: Treatmentmentioning
confidence: 99%
“…Nearly one in four who were fatigued at the onset of the study showed lower levels of fatigue by 1 year, but one in six of the patients who were not initially fatigued recorded increased fatigue. 30…”
Section: Treatmentmentioning
confidence: 99%
“…Fatigue is a significant problem for people with rheumatoid arthritis,1 incorporating physical exhaustion and cognitive impairment, with impacts on lifestyle, roles, relationships and emotions 2 3. RA fatigue is persistent,4 patients feel unsupported by rheumatology teams and rheumatology nurses want help regarding fatigue management 2 5.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health may typically be defined in many ways, such as previous diagnosis of depression [10, 21, 28, 54–56], current levels of dysphoria [54–56] or position on a mental health continuum (e.g. Short Form 36 Mental Health Scale) [10, 21, 22, 28, 57], or use of anti-depressants [10, 21]. Irrespective of the definition, the evidence indicates that higher depression scores, or ratings of dysphoria, in combination with previous history of depression is associated with an exacerbation of, or failure to improve, fatigue [10, 21, 29, 54–57].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the measures used may have substantial impacts on the associations observed if a predictor is differentially associated with distinct dimensions of fatigue [9]. It is notable that few studies have used scales that capture the multidimensionality of fatigue, instead relying on single-item visual analogue scales, or numerical rating scales [5, 10, 24, 26, 27, 29, 30, 37, 41, 49, 54, 56, 57]. Equally, there is no consistency in the definitions and measures used to capture exposures of interest and no single study has investigated all predictors of interest, making it likely that residual confounding exists and precluding the development of an evidence-based causal model/diagram of fatigue.…”
Section: Introductionmentioning
confidence: 99%